How Large is the Border Effect between the United States and China? - Wang, Di; Wang, Zhimin; Xie, Yuying (Asian Economic and Financial Review, 2019)
This study examines the border effect on price variation between the United States and China. A unique data set consisting of exchange rate, four different annual consumer price index series, and geographical position data was obtained for 14 metropolitan areas in the United States and 31 regions in China over the period 2004–2015. Three different regression models were employed to examine the border effect between the United States and China, which was shown to be statistically significant by all three. The distance needed to level the cross-border price dispersion was also estimated and revealed a substantial border effect. Further, to exclude the effect of the nominal exchange rate on cross-border price variation, the border effect was tested using the relative–relative price, but a large border effect remained. Finally, China’s reform of its exchange rate regime in 2005, its entrance into the World Trade Organization in 2001, and both it and the United States’ direct and indirect government interventions during the 2008 financial crisis proved to be possible influences on the border effect between the two countries during the sample period.